Differences in Brain Activity and Body Movements Between Virtual Reality and Offline Exercise: Randomized Crossover Trial - Hee Jin Kim; Jea Woog Lee; Gangta Choi; Junghoon Huh; Doug Hyun Han (JMIR Publications, 2023)
BackgroundVirtual reality (VR) has been suggested to be effective at enhancing physical exercises because of its immersive characteristics. However, few studies have quantitatively assessed the range of motion and brain activity during VR exercises. ObjectiveWe hypothesized that 3D immersive VR could stimulate body movement and brain activity more effectively than standard exercises and that the increased range of motions during 3D immersive VR exercises would be associated with orbitofrontal activation. MethodsA randomized crossover trial was conducted to compare exercises with and without VR. A total of 24 healthy males performed the same motions when exercising with and without 3D immersive VR, and the recorded videos were used for motion analysis. Hemodynamic changes in the prefrontal cortex were assessed using functional near-infrared spectroscopy. ResultsThere were significant differences in the total angle (z=−2.31; P=.02), length (z=−2.78; P=.005), calorie consumption (z=−3.04; P=.002), and change in accumulated oxygenated hemoglobin within the right orbitofrontal cortex (F1,94=9.36; P=.003) between the VR and offline trials. Hemodynamic changes in the right orbitofrontal cortex were positively correlated with the total angle (r=0.45; P=.001) and length (r=0.38; P=.007) in the VR exercise; however, there was no significant correlation in the offline trial. ConclusionsThe results of this study suggest that 3D immersive VR exercise effectively increases the range of motion in healthy individuals in relation to orbitofrontal activation. Trial RegistrationClinical Research Information Service KCT0008021; https://cris.nih.go.kr/cris/search/detailSearch.do/23671